A new species in the subgenus Wilhelmia (Diptera: Simuliidae: Simulium) from Sichuan, China - An, Yuxin; Wang, Yuyu (Zootaxa, 2025)
Simulium (Wilhelmia) xichangense sp. nov. is described based on females from Sichuan province, China. It is the firstly recorded species of the subgenus Wilhelmia in Sichuan province. This species is assigned to the subgenus Wilhelmia and is morphologically most similar to S. (W.) pinnatum Chen, Zhang and Jiang, 2016 from Gansu province in China. A key to the female adults of the subgenus Wilhelmia of China is provided.